PENGARUH CUSTOMER EXPERIENCE DAN BRAND TRUST TERHADAP CUSTOMER LOYALTY - Loga Jevana; Ratnawili Ratnawili (UM. Bengkulu, 2026)
This study aims to analyze the influence of customer experience and brand trust on customer loyalty toward Kahf skincare products among Generation Z on TikTok Shop. The research employed a quantitative approach using a survey of 120 respondents who had purchased Kahf products through TikTok Shop. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that customer experience and brand trust partially and simultaneously have a positive and significant effect on customer loyalty. These findings confirm that a positive shopping experience and strong brand trust are key factors in building customer loyalty among Generation Z in e-commerce platforms. Keywords: Customer Experience, Brand Trust, Customer Loyalty.